Sifat fisik dan kimia mayones dari virgin coconut oil dan air kelapa: Physical and chemical properties of mayonnaise from virgin coconut oil dan coconut water - Wiyani, Lastri; Rasyid, Rismawati; Nurjannah, N; Aladin, Andi; Nirma; Nurhalifa (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Mayonnaise is a form of emulsion that is widely used in food products, for example salads, meatballs, sausages, etc. Mayonnaise can be made by mixing vegetable oil and water with the addition of other components such as egg yolks, sugar, salt, mustard, lime and pepper. The addition of these ingredients will affect the characteristics of the mayonnaise produced. This research aims to determine the best concentration of sugar and mustard in mayonnaise from Virgin Coconut Oil and coconut water in terms of their physical and chemical propeties. Mayonnaise is made by mixing VCO and coconut water, xanthan gum, salt, lime, sugar and mustard. All ingredients were mixed using an ultra turrax tool at a speed of 15000 rpm for 4 minutes to form an emulsion. Variations were made regarding the addition of sugar (0%, 1%, 2%, 3%) and the addition of mustard (0.5%, 1%, 1.5%, 2% and 2.5%). The mayonnaise formed was analyzed for physical and chemical properties. The resulting mayonnaise is stable. The addition of sugar and mustard to mayonnaise will increase viscosity and pH but has no effect on stability and water content. Mayonnaise made with the addition of 3% sugar and 0.5% mustard has a carbohydrate content of 2.51%, a total plate count of 1.8Ãƒâ€”102 colonies/g in accordance with Indonesian National Standard (SNI) 01-4473-1998. However, the protein content (0.17%) and fat (43.19%) are lower than SNI, while the water content (53.34%) in mayonnaise is higher than SNI.